EFEKTIVITAS KEBIJAKAN AFIRMATIF DALAM MENINGKATKAN PERAN PEREMPUAN SEBAGAI AGEN PENGAWASAN POLITIK DI KABUPATEN ACEH TENGGARA - Lusiana; Mustapa Kamil Alga Beruh (CV. Lafadz Jaya, 2026)
Affirmative action policies constitute an essential instrument for enhancing women's participation in political life, including political oversight and electoral supervision. In Indonesia, affirmative action is implemented through regulations requiring at least 30 percent women's representation in political party management and legislative candidacy. Nevertheless, these policies have not fully succeeded in strengthening women's substantive role as political oversight agents, particularly in regions where patriarchal culture remains dominant, such as Southeast Aceh Regency. This study aims to analyze the effectiveness of affirmative action policies in strengthening women's role as political oversight agents in Southeast Aceh Regency. The research employs a qualitative descriptive approach using literature review, document analysis, observation, and interviews involving election administrators, women's activists, academics, civil society organizations, and community leaders. The analysis is based on affirmative action theory, political representation theory, and political participation theory. The findings indicate that affirmative action policies have created broader opportunities for women to participate in election supervisory institutions, participatory monitoring initiatives, and political oversight activities. However, their effectiveness remains constrained by patriarchal culture, limited political education, insufficient leadership capacity, male-dominated political elites, and weak political party support for female cadres. Despite these challenges, women contribute significantly to promoting transparency, accountability, and democratic integrity through election monitoring, civic education, and the prevention of electoral violations. This study recommends strengthening political education for women, enhancing leadership capacity, expanding community-based participatory oversight, and improving the implementation of affirmative action policies to achieve not only numerical representation but also substantive representation in local democracy.